Wonderful Indonesia: Nation Branding From The Perspective of Public Diplomacy - Raka Tantra Pamungkas (Jurnal Studi Diplomasi dan Keamanan, 2015)
Nation branding has invaded almost all aspects of human life, not only for product or corporate, but also increasingly for places. Currently more cities, regions and states have increasingly cooperated with PR firms or branding consultants to achieve their target to build positive image and deliver their message to intended audience, including general public. Indonesia has been in attempt to formulate the best nation brand that can represent what both Indonesian citizens and government desire to have. Tourism is on the first step to account as it clearly shows the greatest potential to improve the positive image of Indonesia’s country of origin. Looking at ‘wonderful Indonesia’ as the country’s nation branding, this paper seeks to scrutinize the issue from the perspective of public diplomacy. Its origins, dynamics, and attempts in improving Indonesia’s branding internationally has proved Indonesia’s intention in exploring its positive attributes – tradition, culture, breathtaking nature amidst various on-going problems domestically.